VALUES OF MORAL EDUCATION IN THE BOOK OF MANHAJ AT-TARBIYYAH AN-NABAWIYYAH LI AT-TIFLI BY MUHAMMAD NUR SUWAID - Nurhamimah Nasution; Azizah Hanum; Junaidi Arsyad (Pena Cendekia Insani, 2025)
This study aims to analyze the moral values in the book Manhaj at-Tarbiyyah an-Nabawiyyah li a?-?ifli by Mu?ammad N?r Suwaid and its relevance to the present. The type of research is qualitative using a library research approach. The data analysis technique in this study is with content or content analysis techniques. The results of this study are divided into four parts : first; the role of parents in children's education, second; morals and children's devotion to parents, third; children's development in terms of faith, worship, society, morals, feelings, physical, intellectual, health, sexual education, and fourth; The method of education is a good example, the right time to provide guidance, be fair and equal to fellow children, fulfill children's rights, pray for children, buy toys, help children to do good and obey, don't reproach! Bringing stories, speaking directly, talking to children according to their intellectual capacity, dialogue, practical experience methods, teaching the personality of the Prophet, accompanying children, instilling joy and happiness into children's souls, instilling a spirit of constructive competition among fellow children and giving awards to the winners, motivating children, praise and flattery, motivating and frightening, fulfilling desires and satisfying children. Based on the researcher's analysis, the values of moral education in the book Manhaj at-Tarbiyyah an-Nabawiyyah li a?-?ifli by Mu?ammad N?r Suwaid are relevant to the current context.